High-contrast tunable unidirectional reflectionless phenomenon near the exceptional points in integrated bulk Dirac semimetal waveguide. (27th August 2021) - Wu, Zhuolin; Zeng, Yi; Liu, Guidong; Wang, Ling-Ling; Lin, Qi
Abstract: We realize the unidirectional reflectionless light propagation in metal-insulator-metal plasmonic waveguide side-coupled with two resonators based on bulk Dirac semimetal (BDS). This phenomenon is observed at exceptional points where the parity-time symmetry is broken, and near perfect absorption is obtained. Based on the dynamic tunability of BDS, the ultra-compact structure with adjustable unidirectional reflectionlessness can be achieved due to low scattering loss. Our results show a potential for developing integrated plasmonic devices such as active mid-infrared sensors, diodes, and absorbers.